(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Social Media platforms such as Facebook, WhatsApp, and Instagram have many avenues for engaging people who have common interests. In 2020, there were about 3.6 billion social media users worldwide and the number is ratcheting daily. Social media addiction is a form of internet addiction characterized by problematic use of social media by people of all ages, including adolescents. The objective of the study is to know the level of social media addiction of college students and to appraise how it is important for college students besides assessing their eagerness in using the same.